2017
DOI: 10.1038/tp.2017.23
|View full text |Cite
|
Sign up to set email alerts
|

Circumcision does not alter long-term glucocorticoids accumulation or psychological effects associated with trauma- and stressor-related disorders

Abstract: Male infants and boys through early adolescence can undergo circumcision either for the sake of upholding religious traditions or for medical reasons. According to both, Jewish as well as Islamic tenets, circumcision is a religious rite symbolizing the bond with God. The World Health Organization (WHO), the United Nations Council (UNC) as well as the American Academy of Pediatrics (AAP), and the Centers for Disease Control and Prevention (CDC) strongly recommend circumcision to promote hygiene and prevent dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 44 publications
1
22
1
Order By: Relevance
“…87 A study of 20 Jewish males in Dresden, Germany found that MC did not alter long-term limbic-hypothalamic-pituitary-adrenal axis activity, subjective stress perception, anxiety, depressiveness, physical complaints, sense of coherence, and resilience. 88 Rather, the study found that an increase in the glucocorticoid levels indicated a healthy lifestyle and appropriate functioning, concluding that the study provided evidence that MC does not promote psychological trauma. An MC opponent commented that the study was underpowered.…”
Section: Painmentioning
confidence: 86%
See 1 more Smart Citation
“…87 A study of 20 Jewish males in Dresden, Germany found that MC did not alter long-term limbic-hypothalamic-pituitary-adrenal axis activity, subjective stress perception, anxiety, depressiveness, physical complaints, sense of coherence, and resilience. 88 Rather, the study found that an increase in the glucocorticoid levels indicated a healthy lifestyle and appropriate functioning, concluding that the study provided evidence that MC does not promote psychological trauma. An MC opponent commented that the study was underpowered.…”
Section: Painmentioning
confidence: 86%
“…The mother was strongly opposed to MC, leading critics to question her approval for this experiment and an assertion that the online report, by an MC opponent, was a fabrication . A study of 20 Jewish males in Dresden, Germany found that MC did not alter long‐term limbic‐hypothalamic‐pituitary‐adrenal axis activity, subjective stress perception, anxiety, depressiveness, physical complaints, sense of coherence, and resilience . Rather, the study found that an increase in the glucocorticoid levels indicated a healthy lifestyle and appropriate functioning, concluding that the study provided evidence that MC does not promote psychological trauma.…”
Section: Physical Harmmentioning
confidence: 90%
“…Infants remember NMC pain only when no anesthesia is used, leading to anesthesia being recommended Taddio et al [133] No evidence of lasting brain changes, nor psychological trauma in neonatally circumcised men Ullmann et al [171] No psychological problems among Swedish schoolboys circumcised for phimosis, apart from "shyness and unwillingness to undress in school gym" Stenram et al [173] [174]…”
Section: Continued Pain and Brain Referencesmentioning
confidence: 99%
“…Examination by the present author of both the 95% and 99% CIs reveals that the confidence intervals for the 30-item Perceived Stress Questionnaire scores (with only 7 circumcised men included since two PSQ response forms were incomplete; see Ullmann et al, Table 2) were unacceptably wide, showing that the mean PSQ scores reported were unreliable. The respective confidence intervals are as follows: Since Ullmann et al stated that, "The PSQ meets the highest national and international quality standards" [1], one can only conclude that the sample size of 7 circumcised men was completely inadequate to obtain reliable PSQ scores. How many of these men had undergone circumcision without analgesia and how many with it?…”
Section: Cortisone (9 Circumcised Men)mentioning
confidence: 99%
“…Yet as will be demonstrated, it is neither logically nor statistically sound to draw any such conclusions on the basis of a null finding [2][3][4], especially when this finding is derived from an underpowered cross-sectional study in which the trend in the data suggest, if anything, that an adequately powered study may have shown exactly the opposite of what the authors claimed [5]. Indeed, as Ullmann et al themselves reported [1].…”
Section: Introductionmentioning
confidence: 99%